2022
DOI: 10.3390/min12030347
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surface Lignite Mines Closure on the Particulates Concentrations in the Vicinity of Large-Scale Extraction Activities

Abstract: The European green deal and energy transition policies and the competition primarily shaped by the high price of carbon dioxide emission allowances and the consistently reduced cost of renewable energy technologies directly affect the coal and lignite extraction industry. Lignite production in Western Macedonia Lignite Centre reduced from 43.2 million tons in 2010 to 10.3 million tons in 2020. This development affects the ambient air quality of the large lignite mine area, as evidenced by the records of 10 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…However, Pavloudakis et al (2022) found that there was a considerable improvement of the air quality in this area over the period 2011-2020 with decreased levels in both PM10 and PM2.5 concentrations and less air pollution episodes [8]. These findings are consistent with the present study.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, Pavloudakis et al (2022) found that there was a considerable improvement of the air quality in this area over the period 2011-2020 with decreased levels in both PM10 and PM2.5 concentrations and less air pollution episodes [8]. These findings are consistent with the present study.…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent with the present study. Moreover, it should be mentioned that many pollution episodes are related to seasonal agricultural activities in the region (e.g., combustion of biomass residues after harvesting) or even the Saharan dust transport events [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focus on Western Macedonia, Greece, which is largely dominated by lignite mining, lignite-fired power plants, and district heating systems [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. These activities are a significant part of the local and national economies but also contribute to environmental pollution in the region.…”
Section: Introductionmentioning
confidence: 99%